Negotiating Islamic Law: The Practice of Inheritance Distribution in Polygamous Marriages in Indonesian Islamic Courts - Nasution, Hotnidah; Muchtar , Ahmad Rifqi (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
This research attempts to look at the allocation of inheritance in polygamous marriages, as adjudicated by the Indonesian Islamic courts, commonly known as the Religious Courts. In a polygamous marriage, the inheritance distribution often faces more complex challenges. This research is grounded in an analysis of decisions from the Religious Courts, including both first-instance and appellate court rulings. The findings indicate that inheritance distribution in polygamous marriages relies not just on the Islamic Law Compilation, but also on the Indonesian Civil Code. Moreover, the judges employed two approaches to resolve disputes: Islamic jurisprudence (fiqh) and the Islamic Law Compilation, which is the codified Islamic law in Indonesia. When the judges referred to the classical texts of Islamic jurisprudence, they allocated the entirety of the inherited properties among the heirs. Negotiation occurred when judges opted for the Islamic Law Compilation instead of classical fiqh, leading them to consider the concept of joint property and distinguish it from the estates. Ultimately, the Appellate Court judges appeared more progressive, taking into account the Indonesian context and ensuring justice for wives in polygamous marriages.